Reducing human immunodeficiency virus stigma: a scoping review of intervention strategies - Qatrannada, Shabrina Arifia; Shaluhiyah, Zahroh; Purnami, Cahya Tri (International Journal of Public Health Science (IJPHS), 2024)
Stigma has become one of the aspects closely associated with human immunodeficiency virus (HIV) and (acquired immunodeficiency syndrome (AIDS), causing adverse effects for those affected. The primary goal of this scoping review is to identify various intervention models aimed at reducing HIV-related stigma. This review follows the PRISMA 2015 guidelines and utilizes sources from three online journal databases: PubMed, ScienceDirect, and Scopus. Search criteria include articles published in the last five years, from 2018 to 2023. Out of the initially retrieved 1,084 articles, 9 articles meeting inclusion criteria were selected for a more in-depth review. Most interventions typically employ a mix of strategies, incorporating diverse degrees of social-ecological involvement. Interventions employing dual strategies and extended durations with multiple sessions have the potential to more effectively reduce stigma. Supporting HIV-safe spaces and encouraging community involvement to understand the link between HIV stigma and the spread of HIV/AIDS in their surroundings can effectively reduce HIV stigma. Overall, most studies included in this review indicate fairly satisfactory outcomes. However, when implementing interventions, it remains crucial to tailor them to the specific location, considering that stigma is a social construct. The development of instruments to measure intervention effectiveness needs to be pursued to comprehensively identify significant intervention impacts.